Three-Dimensional Fully Interlaced Woven Preforms for Composites - Bilişik, Nedim Erman; Bilişik, Havva Esra; Bilişik, Abdulkadir; Şahbaz Karaduman, Nesrin (Sage Publications Ltd, 1 Olivers Yard, 55 City Road, London Ec1Y 1Sp, England, 2013)
The aim of this study was to develop three-dimensional (3D) fully interlaced and semi-interlaced representative woven preform structures and to understand the effects of weave pattern and number of layers on 3D woven structures. Various 3D woven preforms were developed. Data generated from these structures included yarn angle, yarn-to-yarn space and density, yarn length and crimp. It was shown that the weave patterns affected the 3D woven preform structures. The yarn-to-yarn spaces of the 3D fully interlaced and semi-interlaced structures were high compared to the traditional 3D woven structures (orthogonal, through-the-thickness and angle interlock) in fabric width due to the interlacement. The 3D plain, twill and satin structures resulted in warp angle (w) in fabric length and filling angle (f), and interlaced z-yarn angle (zi) in fabric width due to the warp-filling and warp-z-yarn interlacements. The weave patterns slightly affected the yarn angles. On the other hand, it was observed that the number of layers considerably affected the z-yarn arc length and the z-yarn length in thickness in the 3D woven structure. The interlacement on 3D plain, twill and satin woven structures resulted in warp crimp, filling crimp and z-yarn crimp. The crimps in the 3D structure fully interlaced and semi-interlaced woven structures slightly depended on the types of weave pattern and the number of layers.
Keywords: three-dimensional representative fully interlaced woven preform; three-dimensional plain woven preform; three-dimensional twill woven preform; three-dimensional satin woven preform; z-yarn crimp; textile composites; üç boyutlu temsilcisi tamamen taranmış dokuma preform; üç boyutlu düz dokuma preform; üç boyutlu dikiş dokuma preform; üç boyutlu saten dokuma preform; z-iplik kıvrımı; tekstil kompozitler